1995
DOI: 10.1111/j.1744-6570.1995.tb01774.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Self‐regulatory Coping Orientation on Newcomer Adjustment and Job Survival

Abstract: In a field experiment new hires to entry‐level service jobs were randomly assigned to either a comparison group, which received information warning of negative aspects of the job and information about specific coping behaviors, or to an experimental group, which received the same information as the comparison group, plus training in cognitive restructuring and positive self‐talk, and statements to bolster self‐efficacy. It was expected that the experimental group would exhibit less turnover and report higher l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
44
0
5

Year Published

1997
1997
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(51 citation statements)
references
References 40 publications
2
44
0
5
Order By: Relevance
“…499,[509][510][511][512] • Institutional socialisation tactics were also found to have a positive impact on organisational commitment. 492,509,510,512,513 • Wesson and Gogus 514 found that a computerbased orientation programme had a negative impact on job satisfaction, organisational commitment and levels of later socialisation.…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations
“…499,[509][510][511][512] • Institutional socialisation tactics were also found to have a positive impact on organisational commitment. 492,509,510,512,513 • Wesson and Gogus 514 found that a computerbased orientation programme had a negative impact on job satisfaction, organisational commitment and levels of later socialisation.…”
Section: Resultsmentioning
confidence: 97%
“…• Studies by Waung, 512 Jones 509 and Chatman 499 concluded that institutionalised socialisation tactics had a positive impact on intention to remain with the organisation and, thus, reduced turnover. However, Waung 512 found that providing relevant and potentially negative information about the job during the process of orientation did adversely affect some new recruits, who left the organisation in the first few weeks.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Thirdly, given that self-efficacy predicts choice of career, occupational interests, perseverance in the face of difficulties and personal effectiveness (Bandura 1986;Krueger and Dickson 1994;Waung 1995), it must also be related to entrepreneurial activity. Finally, since the incentive for acting is greater when entrepreneurs believe that their actions will have achievable outcomes, self-efficacy is an important determinant of successful entrepreneurial behaviours.…”
Section: Self-efficacymentioning
confidence: 99%